Exploiting bacterial iron acquisition: siderophore conjugates - Ji, Cheng (Future Med Chem, 2012)
Siderophores are chelators synthesized by bacteria and fungi to sequester iron, which is essential for virulence and pathogenicity. Since the process involves active transport, which is highly regulated, remarkably efficient and often microbially selective, it has been exploited as a Trojan Horse method for development of microbe-selective antibiotics. Siderophores also have significant potential for the development of imaging contrast agents and diagnostics for pathogen-selective detection. These promising results demonstrate the versatility of natural and synthetic microbial iron chelators and their potential therapeutic applications.